Relationship of special and functional preparedness of freestyle wrestlers at different stages of sports training - Volkov, L.; Zakharkiv, S. (Slobozhanskyi herald of science and sport, 2019)
The presented experimental data indicate that at all stages of the long-term training of freestyle wrestlers between the ages of 11-12 years old and 17-18 years old there are reliable relationships between the indicators of special and functional readiness. The greatest numbers of reliable relationships have tests on special preparedness - "rushing on the wrestler's bridge in 1 minute", "coups on the wrestler's bridge in 1 minute". The conducted studies confirm the reliably high interconnection of the components of special and functional preparedness when training adolescents and young men in wrestling. Separate components of these types of training change the information content depending on the stages of preparation, require changes in the total and selective amounts of training loads.